2005
DOI: 10.1111/j.1467-842x.2005.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

An accelerated hepatitis B vaccination schedule for young drug users

Abstract: Objective: Jo determine completion rates for an accelerated hepatitis B vaccine (HBV) program among a population of young drug users. Design: Between January 2001 and May 2002, a three‐dose course of HBV vaccine (0, 7 and 21 days) was offered free to all drug users (aged 22 years or younger) accessing two outreach sites of a youth‐focused support and drug treatment service in metropolitan Melbourne, Australia. Clients were offered vaccination in any safe environment of their choice. An audit was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…12 Recent efforts have focused on contingency management 34,37,38 and enhanced outreach [39][40][41] to improve HBV vaccination uptake and completion in this group. There is some evidence that rapid schedules may be cost effective 42 for improving completion 25,43,44 although evidence of long-term immunogenicity in this group is still lacking. 11,45 Vaccine-induced immunity to HBV among anti-HCV and anti-HBc negative participants was associated with a history of incarceration but not with recent NSP attendance or lifetime OST, highlighting important missed opportunities for vaccination in these settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Recent efforts have focused on contingency management 34,37,38 and enhanced outreach [39][40][41] to improve HBV vaccination uptake and completion in this group. There is some evidence that rapid schedules may be cost effective 42 for improving completion 25,43,44 although evidence of long-term immunogenicity in this group is still lacking. 11,45 Vaccine-induced immunity to HBV among anti-HCV and anti-HBc negative participants was associated with a history of incarceration but not with recent NSP attendance or lifetime OST, highlighting important missed opportunities for vaccination in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…22 PWID were also recently identified as a population of interest in Australia's first National HBV Strategy 23 which recommended education and opportunistic testing and vaccination of young people with multiple risk factors. Targeted immunisation programs have been successful when administered using rapid schedules, 11,24,25 focussed on young people 25 and provided free of charge. 26 We aimed to assess the current epidemiology of HBV among PWID in Sydney, including HBV vaccine-induced immunity and prior infection, and factors associated with HBV status.…”
mentioning
confidence: 99%
“…48 Wright et al described the vaccine uptake in a population of homeless drug users in a single primary care centre. The standard schedule (0.1.6 months) that was offered in 1999 changed to the primary part of a super-accelerated 0.7.21-day vaccination schedule in 2000.…”
Section: Drug Usersmentioning
confidence: 99%
“…Previous studies among DUs have reported completion rates of hepatitis B vaccination, varying from low completion rates (20%-31%;Des Jarlais et al, 2001;Christensen et al, 2004;Seal et al, 2003), to intermediate (41%-63%; Christensen et al, 2004;Lum et al, 2003;Ompad et al, 2004;McGregor, Marks, Hayward, Bell, and Slack, 2003;Van Houdt et al, 2006;Van Steenbergen, 2002), to high-compliance rates (66%-88%; Altice, Bruce, Walton, and Buitrago, 2005;Budd, Robertson, and Elton, 2004;Christensen et al, 2004;Des Jarlais et al, 2001;Lugoboni et al, 2004;Rogers and Lubman, 2005;Seal et al, 2003;Quaglio et al, 2002) depending on the use of different vaccination schedules, onsite vaccination possibilities, and the use of monetary incentives. However, only some of these studies identified social-demographic factors (age, ethnic background, and homelessness), and risk factors concerning drug use (i.e., injecting drug use) associated with vaccine completion (Altice et al, 2005;Lum et al, 2003;Ompad et al, 2004, Seal et al, 2003.…”
mentioning
confidence: 96%